Contaminant fungi in processed peanuts - Costa, Thâmara Cristina de Oliveira; Santos, Wallisson Felipe Giliolli; Machado, Simone Silva; Blanco, Angel José Vieira (Seven Editora, 2024)
Peanuts (Arachis hipogea L) are a plant cultivated in many parts of the planet and are considered a relevant food crop, with many minerals and vitamins in their grains, as well as fats and proteins, which are important for human health. In underdeveloped or developing countries, peanuts represent an important source of income for many families, and can be used by the oil and animal feed industries. Despite being a low-cost food source, peanuts can pose risks to human health, as they are subject to contamination by mycotoxin-producing fungi. Mycotoxins are heat-resistant compounds, which are not completely eliminated after heat treatment, meaning that even when roasted or cooked, peanut kernels can cause inconvenience to those who consume them. Cases involving allergies, necrosis of organs such as kidneys and liver, and even carcinogenesis, caused by mycotoxins, are widely recorded in the medical literature. This research work aimed to evaluate the occurrence and diversity of mycotoxin-producing fungi in peanut kernels, sold in closed packages in the city of Inhumas. BDA medium (potato dextrose agar) was used for the isolation of fungi. The sampling consisted of 200 grains, belonging to five different brands. Half of the samples were disinfected with 1% sodium hypochlorite. Morphological characteristics (macroscopic and microscopic) of the colonies were used to identify the genera to which the isolated fungi belong. The results revealed a high rate of fungal contamination in peanut kernels, with Fusarium being the predominant fungus. Fungi of the genera Rhizopus and Aspergillus were also identified in the samples. It is expected that the results obtained will contribute to increase the information on the presence of toxigenic fungi in peanut kernels, helping in the decision-making of regulatory agencies and consumers who use this important food source. DOI:https://doi.org/10.56238/sevened2024.023-024